Über die unregelmäßige Form yǝbe im Altäthiopischen. II - Voigt, Rainer (Aethiopica, 2000)
Classical Ethiopic yǝbe ‘he said’ (with suffixes yǝbel-) is irregular with respect to the loss of the second and third radical of the root (√bhl) as well as especially to its preterite meaning. The attempt has been made to regard this unique feature as Proto-Semitic and connect it with the morphological difference between the narrative yáqtul and the jussive yaqtúl as known from Classical Hebrew å´śēm ‘may he put’ as against (a-)´åśęm ‘(and) he put’. Accordingly, yǝbe would represent an old narrative which would be all the more plausible since this form is very often — as in Hebrew — preceded by wa-. In VOIGT (1997) an argument against this view was made based on the difficulty of deriving yǝbe(lV) from *yǝb(h)al. An etymo-logical investigation of all kinds of long e in Classical Ethiopic as presented there does not support this derivation. It is better to explain yǝbe as a historical present form often ex-pressing an accompanying action (§ 3, IV, b). In order to understand the phonological processes better, several Ethio-Semitic reflexes of the root √bhl are investigated. Special attention is devoted to the multifarious forms in Tigre which can be split up into four different paradigms. Through the derivation of the Tigre forms one can obtain grounds for tracing Classical Ethiopic yǝbe back to a present form too (§ 4). A parallel is found in Beɗauye where the preterite of the verb ‘to say’ is originally a present form (§ 5). Thus we are able to assign the specific Classical Ethiopic development to Cushitic influence. Since yǝbe ‘he said’ goes back to the Proto-Ethiopic present form *yǝbah:ǝl, the present form yǝbǝl ‘he says’ must have the same origin (§ 6).